2018
DOI: 10.1016/j.rmed.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Shorter telomeres in non-smoking patients with airflow limitation

Abstract: Telomere shortening is associated with airflow limitation independent of smoking status. Weather premature ageing or biologically determined shorter telomeres are responsible for this finding remain to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…A somewhat surprising finding was that the multivariable analysis showed that cumulative smoking exposure in ever smokers did not affect the relationship between TL and lung function at any age. Yet, this observation is in keeping with the results of a meta-analysis of 18 longitudinal cohorts by Bateson et al indicating that smoking does not accelerate leucocyte telomere attrition (48), and with those of Cordoba et al showing that telomere shortening is associated with the airflow limitation independently of the smoking status (16). Importantly, it does not detract from the firmly established view that smoking is a key environmental risk factor for COPD (3); it only indicates that smoking per se does not influence the relationship between TL and lung function.…”
Section: Interpretation Of Novel Findingssupporting
confidence: 89%
See 2 more Smart Citations
“…A somewhat surprising finding was that the multivariable analysis showed that cumulative smoking exposure in ever smokers did not affect the relationship between TL and lung function at any age. Yet, this observation is in keeping with the results of a meta-analysis of 18 longitudinal cohorts by Bateson et al indicating that smoking does not accelerate leucocyte telomere attrition (48), and with those of Cordoba et al showing that telomere shortening is associated with the airflow limitation independently of the smoking status (16). Importantly, it does not detract from the firmly established view that smoking is a key environmental risk factor for COPD (3); it only indicates that smoking per se does not influence the relationship between TL and lung function.…”
Section: Interpretation Of Novel Findingssupporting
confidence: 89%
“…Telomerase mutations and telomere attrition are described in alveolar type II and endothelial cells in patients with severe emphysema (34)(35)(36) and in mice models of smoking exposure (37). Other studies reported shortened telomeres (15) in old patients with COPD vs. controls (12,13,15,16) and a modest association between TL and FEV 1 % ref. (13), albeit the latter was not reproduced in other investigations (13-15, 38, 39).…”
Section: Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors refer to a separate study reporting that COPD patients have significantly shorter blood leucocyte telomeres than healthy controls (12) and Córdoba-Lanús et al suggest that airflow limitation is associated with shortened telomere lengths (13). However, Doherty et al did not report airflow and other lung function parameters, presence or absence of COPD, or other comorbidities associated with altered telomere length in their cohort.…”
Section: Confounding Effectsmentioning
confidence: 96%
“…In most somatic cells, TL shortens with each cellular division until a critical point, beyond which cells enter a stage of replicative senescence. In adult populations without HIV, shorter leukocyte TL has been associated with reduced lung function [ 11 , 12 ], airflow limitation in nonsmokers [ 13 ], chronic obstructive pulmonary disease (COPD) [ 14 ], and asthma [ 15 ]. In the context of HIV, the infection itself is associated with shorter leukocyte TL in adults without and with respiratory diseases [ 16–19 ], and in the latter, shorter TL was also measured in small airway epithelial cells [ 20 ].…”
mentioning
confidence: 99%